Lung Protective Ventilation in Brain-Injured Patients: Low Tidal Volumes or Airway Pressure Release Ventilation? - Garg, Ravi (Journal of Neuroanaesthesiology and Critical Care, 2020)
The optimal mode of mechanical ventilation for lung protection is unknown in brain-injured patients as this population is excluded from large studies of lung protective mechanical ventilation. Survey results suggest that low tidal volume (LTV) ventilation is the favored mode likely due to the success of LTV in other patient populations. Airway pressure release ventilation (APRV) is an alternative mode of mechanical ventilation that may offer several benefits over LTV in this patient population. APRV is an inverse-ratio, pressure-controlled mode of mechanical ventilation that utilizes a higher mean airway pressure compared with LTV. This narrative review compares both modes of mechanical ventilation and their consequences in brain-injured patients. Fears that APRV may raise intracranial pressure by virtue of a higher mean airway pressure are not substantiated by the available evidence. Primarily by virtue of spontaneous breathing, APRV often results in improvement in systemic hemodynamics and thereby improvement in cerebral perfusion pressure. Compared with LTV, sedation requirements are lessened by APRV allowing for more accurate neuromonitoring. APRV also uses an open loop system supporting clearance of secretions throughout the respiratory cycle. Additionally, APRV avoids hypercapnic acidosis and oxygen toxicity that may be especially deleterious to the injured brain. Although high-level evidence is lacking that one mode of mechanical ventilation is superior to another in brain-injured patients, several aspects of APRV make it an appealing mode for select brain-injured patients.
Keywords: pressure-controlled inverse ratio; airway pressure release ventilation; biphasic positive airway pressure; intracranial pressure; cerebral hemodynamics